The use of the pre-engineering inventory as an aid in counseling prospective engineering students at Colorado Agricultural and Mechanical College - Eyestone, Robert H., author; Comstock, George A., advisor; Heilig, Herb, committee member; Towne, Charles F., committee member; Lewis, Robert L., committee member; Madison, M. Leslie, committee member (Colorado State University. Libraries, 1948)
To view the abstract, please see the full text of the document.
Keywords: Engineering -- Study and teaching; Counseling; Ability -- Testing